PERAN LEMBAGA KEUANGAN MIKRO (LKM) TERHADAP KINERJA EKONOMI KABUPATEN JOMBANG - Atut Frida Agustin (Jurnal Ekonomi Pembangunan, 2011)
The objective of this study were: 1) To know the potential of Microfinance Institution (LKM) in Jombang Regency, 2) To know the role of Microfinance Institution (LKM) towards economic performance in Jombang Regency, 3)To know the needs of Microfinance Institution (LKM) Development in increasing LKM roles on the Jombang Regency economy. The results showed: First, the overall number of Microfinance Institutions (MFIs) in as many as 425 Jombang spread in 21 regencies. The regency which had LKM at most in Jombang regency for 154, the second was Ngusikan Regency. Second,The results of Econometric analysis were able to concluded that the amount of LKM, LKM capital, and the volume of bussiness impacted to the variable of economic growth in Jombang Regncy. Third, easy and soft loan had a degree of interest by 87% whereas direct aid only had a degree of interest of 13%. Meanwhile, institutions which was more effective to provide capital loans on LKM development was institutional in rural areas, for example, through another microfinance.